การให้แสงเสริมจากหลอด LED แก่กระชายดำที่ปลูกในโรงเรือน - หลอดทองหลาง กัญตนา; มะโนชัย เบญญา; จุลกะ ปริยานุช (Thai Journal of Science and Technology, 2019)
Study on using supplemental LED light for black ginger cultivation under greenhouse condition. Completely randomized design (CRD) with 4 treatments, i.e. 2 white light LEDs (2W), LED white: blue light ratio 2: 1 (2W1B) and LED white: blue light ratio 1: 2 (1W2B) compared with planting non-LED, supplemental light for 3 hours before 6 a.m. and 3 hours after 6 p.m. The plant growth, active compounds, antioxidant activity, anthocyanin, total phenolic compounds and 5,7-dimethoxyflavone were recorded. The results revealed that growth parameters, i.e. the plant height, number of clump, leaf greenness, fresh and dry weight of rhizome, and percentage of crude extract were not significantly different. The data of active compounds showed the best results of total phenolic compounds and 5,7-dimethoxyflavone content at non-LED light, supplemented with the mixture of white light tube: blue light tubes (2: 1) and (1: 2), anthocyanin highest at non-LED light, supplemented with 2 white light LEDs (2W) and the mixture of white light tube: blue light tubes (1: 2).